Poster Edukasi Obat Paten Dan Generik (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The goals of treatment are to protect and restore health and maintain and improve quality of life. Therefore, the community needs access to affordable and good quality medicines so that the cost of treatment is more affordable economically, without reducing the quality or quality of the drugs. The problem is that currently there are not many people who are interested in generic drugs because they think that low drug prices are synonymous with low drug quality. This community service activity aims to provide education to the public about the differences between generic drugs and patented drugs which in turn encourages people to use generic drugs to reduce medical costs. The educational method used is through the distribution of brochures at 25 K24 pharmacy outlets in the Yogyakarta area. The results of this activity received a very good response from the pharmacy because they felt it helped in providing this information. The community's acceptance of this activity is also very good so that the education process can also be carried out directly to patients while at the pharmacy